Ant ecology - Lach, Lori.; Parr, Catherine L.; Abbott, Kirsti L. (Oxford : Oxford University Press, 2009)
The incredible global diversity of ants, and their important ecological roles, mean that we cannot ignore the significance of ants in ecological systems. 'Ant Ecology' takes the reader on a journey of discovery from the beginnings of ants many hundreds of thousands of years ago, through to the makings of present day distributions.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Ants -- Ecology; Ants